Experimental Study of the Effect of Exhaust Gas Recirculation (EGR) and Injection Timing on Emitted Emissions at Idle Period - Chaichan, Miqdam Tariq (Al-Khwarizmi Engineering Journal, 2017)
Abstract Heavy-duty diesel vehicle idling consumes fossil fuel and reduces atmospheric quality at idle period, but its restriction cannot simply be proscribed. A comprehensive tailpipe emissions database to describe idling impacts is not yet available. This paper presents a substantial data set that incorporates results from DI multi-cylinders Fiat diesel engine. Idle emissions of CO, hydrocarbon (HC), oxides of nitrogen (NOx), smoke opacity, carbon dioxide (CO2) and noise have been reported, when three EGR ratios (10, 20 and 30%) were added to suction manifold. CO2 concentrations increased with increasing idle time and engine idle speed, but it didn’t show clear effect for IT advancing. CO concentrations increased for all the studied tests with adding EGR. HC concentration increased with idle time advance, but it reduced with increasing idle speed and advancing engine IT. NOx concentrations reduced with adding EGR for all the tested variables. NOx increased with increasing idle time, engine speed and advancing IT. Smoke opacity increased with increasing idle time and retarding IT. Using EGR increased opacity for all tested cases. EGR addition reduced engine noise for all tested cases. Engine noise increased with increasing idle time and retarding IT.